Oral rehabilitation in patient with occlusal factors-related temporomandibular disorder - Salcedo Nuñez, Fernando A. (2013)
We present the following case report: Female patient, 51 years of age, partial edentulous malocclusion class I go to the clinic to graduate Oral Rehabilitation area because of the constant noise and with reduced pain periauricular masticatory function. The aim of this case report was the diagnosis and treatment of the disorder Temporomandbular held clinically and radiologically by MRI of the temporomandibular joint reaching unilateral diagnosis of disk displacement with reduction right, so treatment is initiated in a first step to peace through a displacement device mandibular occlusal (DODAM) followed by an occlusal stabilization splint and then continue with fixed prosthetic rehabilitation. The conclusion of this case report is to give importance to joint stability through the use of braces before starting treatment of prosthetic rehabilitation in cases of Temporomandibular Disorder presenting disk displacement with reduction, knowledge of occlusal factors allow the clinician guided in the diagnosis and treatment of temporomandibular disorder considering the conditions of each individual.